DIAGNOSIS DE LA COMUNICACIÓN ORGANIZACIONAL DEL CENTRO INTEGRAL DE PROMOCIÓN Y EMPLEO DE LA MUJER CIPEM-BABAHOYO - MIRANDA TOBAR ODALYS MAYERLY (2024)
This study will cover the diagnosis of organizational communication of the Comprehensive Center for the Promotion and Employment of Women CIPEM – Babahoyo 2024, focusing on examining the situation of communication within the organization, to recognize its importance in a context where interconnection and Collaboration is key to progress. This not only benefits employees of the institution, but also all beneficiaries who are participants in CIPEM. It focused on exploring the organizational communication of said institution and analyzed the current situation as well as seeking to promote a collaborative, transparent environment to achieve effective results within the organization, in line with its commitment to promoting the comprehensive development of women in Babahoyo.